How patients adjust psychologically to the experience of head and neck cancer: a grounded theory - Calver, Louise (2018)
Introduction: Head and neck cancer presents unique challenges to patients due to its effects on vital human functions and its potential for facial disfigurement. Literature discussing the associated psychosocial difficulties is growing However, there is currently limited understanding about how patients may adjust to the physical, functional, and psychological effects experienced as a result of head and neck cancer and its treatment. Existing adjustment theories have not been grounded in patient data and often minimise the roles of emotions and other people.